5 - Feminist Postproverbial as a Panacea for Decolonising African Feminist Scholarship - Oyeleye, Olayinka Adebimpe (Journal of Higher Education in Africa, 2022)
Part of the weakness of feminist scholarship in Africa is its inability to turn knowledge generated in universities (episteme) into popular opinion (doxa), thereby creating a dislocation between academic epistemic space and mainstream society. This article addresses how a decolonised feminist scholarship can ground equality by reconstructing doxa from traditional knowledge, as found in proverbs. In accordance with the AU Agenda 2063, it aims to shatter the economic, social and political glass ceiling that has restricted women’s progress by undercutting the imperialist language of patriarchy. It purposes to do this using a medium it calls feminist postproverbials.